ANALISIS DIKSI, BAHASA FIGURATIF, DAN CITRAAN SERTA NILAI PENDIDIKAN KARAKTER DALAM KUMPULAN CERPEN PEREMPUAN YANG DISUNTING GELOMBANG KARYA INDRA TRANGGONO - Khusnul Lusita (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2018)
This study aims to describe: diction, figurative language, images, and the value of character education in Women's short story collection edited by waves. This study is a qualitative descriptive study with a stylistic approach. The subject in this study was a collection of Women's short stories Edited by Indra Tranggono's Waves and articles related to stylistic studies. Objects in the research in the form of texts containing diction, figurative language, images, and the value of character education in a collection of short stories of Women Edited Waves. This research place is not related to the place, but in the form of short story text. The time of this study starts from December 2017 to August 2018. Data collection techniques use library techniques, read, and record. Data validation in this study uses triangulation theory. Data analysis in this study uses content analysis. The results obtained from the study indicate that: (1) diction in the collection of short stories of women who edited the wave as a whole amounted to 30 data (2) figurative language in a collection of short stories The Edited Waves as a whole amounted to 68 data (3) images in the collection of the Women Edited Shortwaves as a whole amounted to 44 data (4) the value of character education contained in the collection of short stories Women Who Edited the Waves as a whole are 8 values. Keywords: Diction, Figurative Language, Imagery and Character Education Value